Penerapan Prinsip Pemuridan Elia dalam Pendidikan Agama Kristen - Soeliasih Soeliasih (Jurnal Teologi Berita Hidup, 2019)
Elijah was one of the prophets of the nation of Israel who experienced the terrible use of God. Through his ministry, the Israelites experienced a great revival. The success of Elijah's ministry did not reach himself, but he had duplicated it to his student named Elisha, even Elisha became a greater prophet than Elijah. The success of discipleship Elijah the prophet needs to be an example for God's servants today in carrying out Christian religious education. This study seeks to find the principles of discipleship Elijah the prophet to apply to discipleship in the present. As a result of this research, it was found several qualifications of religious educators in Elijah, including aspects of spirituality, mentality, personality, and managerial. Abstrak: Elia adalah salah satu nabi bangsa Israel yang mengalami pemakaian Allah secara dahsyat. Melalui pelayanannya bangsa Israel mengalami kebangunan rohani yang besar. Keberhasilan pelayanan Elia tidak sampai pada dirinya sendiri, namun ia telah menduplikasikannya kepada muridnya yang bernama Elisa, bahkan Elisa menjadi nabi yang lebih hebat daripada Elia. Keberhasilan pemuridan nabi Elia perlu menjadi contoh bagi hamba-hamba Tuhan pada masa sekarang dalam menjalankan pendidikan agama Kristen. Penelitian ini berusaha menemukan prinsip-prinsip pemuridan nabi Elia untuk dapat diterapkan bagi pemuridan pada masa sekarang. Sebagai hasil dari penelitian ini ditemukan beberapa kualifikasi pendidik agama dalam diri Elia, meliputi aspek spiritualitas, mentalitas, personalitas, dan manajerial.